2020 16th International Conference on Network and Service Management (CNSM) 2020
DOI: 10.23919/cnsm50824.2020.9269117
|View full text |Cite
|
Sign up to set email alerts
|

Network Coding Aware User Plane for Mobile Networks

Abstract: In this paper, we propose a network coding (NC) enabled transmission strategy in the User Plane (UP) of mobile backhaul for networks operators. In the proposed method, NC provides robustness against the transport network failures, so that there will not be any more processing for re-transmission by the User Equipment (UE) in comparison to traditional approaches where re-transmissions are performed by UE applications. Our simulation results indicate that an average 1% loss ratio in the backhaul link creates 59.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The authors in [20] used NC as a potential solution to improve end-to-end latency and reliability, focusing on the Integrated Access Backhaul (IAB) networks introduced by 3GPP. It has been shown that NC of UP provides a visible improvement in application performance in lossy backhaul links [21]. However, the work in [21] does not consider the asymptotic behaviour of the approach and also lacks comparisons with different implementations of RAN functions (e.g., with caching) in UP.…”
Section: Related Work and Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors in [20] used NC as a potential solution to improve end-to-end latency and reliability, focusing on the Integrated Access Backhaul (IAB) networks introduced by 3GPP. It has been shown that NC of UP provides a visible improvement in application performance in lossy backhaul links [21]. However, the work in [21] does not consider the asymptotic behaviour of the approach and also lacks comparisons with different implementations of RAN functions (e.g., with caching) in UP.…”
Section: Related Work and Motivationmentioning
confidence: 99%
“…It has been shown that NC of UP provides a visible improvement in application performance in lossy backhaul links [21]. However, the work in [21] does not consider the asymptotic behaviour of the approach and also lacks comparisons with different implementations of RAN functions (e.g., with caching) in UP.…”
Section: Related Work and Motivationmentioning
confidence: 99%
See 1 more Smart Citation